Transformation of Human Resource Management in Islamic Education: Problems, Global Challenges, and Future Prospects - Hary Nurdi; Husnul Yaqin; Hamdan Hamdan; Hidayat Ma'ruf (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
Human resource management in Islamic education has become a strategic issue in improving the quality, competitiveness, and sustainability of educational institutions in the modern era. This article aims to analyze the transformation of human resource management in Islamic education by focusing on major problems, global challenges, and future development prospects. This study employs a qualitative approach using library research methods through the collection of books, scientific journals, academic articles, and relevant documents related to Islamic educational management and human resource development. Data were analyzed using content analysis techniques to identify important themes and concepts associated with the transformation of human resource management in Islamic education. The findings indicate that Islamic educational institutions continue to face several major problems, including limited teacher professionalism, inadequate digital competence, weak organizational leadership, and insufficient welfare systems for educators. Global challenges such as digital transformation, educational competition, technological disruption, and changing student characteristics have intensified the need for strategic reform in educational management. However, Islamic education also possesses strong future prospects through the integration of Islamic values, digital innovation, continuous professional development, and transformational leadership models. The novelty of this study lies in its integrative analysis that combines the dimensions of organizational transformation, global educational challenges, and value-based human resource development within the context of twenty-first-century Islamic education